A phenomenological approach to sufi culture, ritual structure and its subjective experience in Kādirîhâne - Güner, Burçin Bahadır (Graduate School, 2022)
Sufi rituals have been an important part of cultural and religious life in the Ottoman period. At the beginning of the 20th century, it is known that there were approximately 400 Sufi lodges (tekke) of various orders (tarikat) in İstanbul. In 1925, all Sufi lodges were closed and their activities were banned by the Turkish Republic. Even though they have disintegrated, some of them have been able to continue their traditions. Today, several tarikat perform their rituals and ceremonies. This study examines the Kadirî dhikr ritual in Istanbul. The Rûmî branch of the Kadirî order was established by pîr İsmail Rûmî in the early 17th century. The Kadirîhâne that he built in İstanbul, Tophane in 1631 was later considered as the center tekke (âsitâne) of the Kadirî order in Ottoman geography. Rûmî Kıyam Usûlü or Kıyam Zikri/Ayini is the name of the weekly public ritual among various other rituals and ceremonies. The purpose of this study is to understand the form and structure of the ritual in conjunction with the surrounding culture, and especially to describe the subjective experience of the participant. The study incorporates fieldwork, ethnography, transcription, translation, musical analysis and phenomenological description. In order to grasp the essence of the ritual, the study follows an outside-in path. First, it categorizes and explains the contents of the ritual in the context of the Sufi culture at the Kadirihane. Then, the author describes the ritual first from the third and then the first person's point of view in dedicated chapters. These methodological steps and their requirements are discussed in the first introductory chapter. Chapter 2, Ritual Content, presents the culture (lifeworld) around the ritual. With a phenomenological stance, it categorizes certain concepts from the ritual and explains them with reference to the culture and related literature. The first category, processual, explains the formal organization of the ritual; while the şeyh/postnişin conducts the ritual, participants establish an ostinato polyphony by providing rhythmical chants (dervişler) and songs/recitations (zakirler). The next category, procedural, focuses on what a regular participant performs and/or perceives in the ritual. In this way, certain concepts and behaviors are examined in and out of the ritual. The description in the next chapter builds on this ritual understanding. Chapter 3, Ritual Structure, is a musicological analysis and an objective description of the ritual. This Sufi ritual is a participatory performance and does not allow an outside observer. This means that the observer naturally becomes a part of the zikr circle. However, every detail of the âyin is described, transcribed and analyzed in depth from the perspective of a third person. The weekly ritual consists of Kuud (sit) and Kıyam (stand) sections. First section, Kuud, starts with the Evrâd-ı Şerif, a composed monophonic and axial group chanting that takes approximately 15 minutes. The text is known to be composed by the pîr Abdülkâdir Geylânî (d. 1165), the founder of the Kadirî order. It starts with some verses from the Quran and the rest consists of various salavats (divine blessings and salutations) upon the Prophet Muhammed. Then, participants start to chant La ilahe illallah (There is no god but Allah). While participants (dervişler) chant this phrase, musicians (zakirler) perform songs and recitations over the ostinato of the chant. Lastly, after the Kelime-i Tevhid, one zakir performs a durak ilahisi that allow participants to rest (durak) before standing up for Kıyam. As all participants stand up, they begin to perform a cumhur ilahi and then continue with another ilahi: kıyam durak. After this point, participants perform 5 divine phrases (esmâ) (Hayyul Kayyum Allah; Hay; Allah Allah Hay; Allah and Hu) in succession with metrical sways, while zakirler sing over them. The âyin is concluded with the Verse of Light (Nur 24/35) from the Quran. In Chapter 4, Ritual Experience, the author shares his subjective experience to show the dynamics of meaning and the sense of ritual. Therefore, the phenomenological description takes the form of an intimate narrative. This narrative description takes into account all multisensory details and their connotations. Also, all texts are interpreted from the inside of the ritual participation and performance. As a conclusion, chapter 5 summarizes all findings of the thesis. The concept of zikir, as being the main motivational concept for ritual, precedes both structure as well as the experience of it. The reciprocity between God and Human is symbolized with the rememberer and the remembered. The encounter with the being is presented as the ultimate goal of the zikir. Also, the processual form of the ritual symbolizes propriety (edep) and beauty (güzel) both of which lead one to the union (vahdet) with God.
Kādirîhâne'deki tasavvuf kültürüne, âyin yapısına ve onun öznel deneyimine fenomenolojik bir yaklaşım
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: phenomenology of religion; din fenomenolojisi; sacred music; dini müzik; ethnomusicology; etnomüzikoloji; musical analysis; müzik analizi; Turkish religious music; Türk dini müziği